Analisis Pengaruh Program Keluarga Harapan (PKH) Terhadap Penanggulangan Kemiskinan di Kecamatan Balubur Limbangan Kabupaten Garut - Rikna Auliah; Thresna Irijanto (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2021)
Family Hope Program (PKH) on Poverty Reduction in Balubur Limbangan, Garut Regency. This type of research is quantitative descriptive. The population in this study was PKH participants in Balubur Limbangan District. The number of samples in this study were 95 people. The sampling technique in this study uses stratified random sampling. Data collection technique susing field research (Field Research) consisting of interview sand questionnaires (questionnaire research) and library research. The measurement scale uses a likert scale. In the analysis of data using a simple linear regression test using the E-views 10 program. The research program through the distribution of question naires using descriptive analysis illustrates the general Family program in Balubur Limbangan, Garut Regency, which has been running well. This can be seen from every implementation process that runs smoothly. From the results of research on the influence of the Family Hope Program (PKH) on poverty reduction based on the educational aspect which has an important meaning on reducing the poverty level by a percentage of 63.4%, while based on the health aspect has a significant effect on reducing the poverty level with a result of 71.5%.